Ferula (Ferula elaeochytris) as a phytoestrogen: Use of Ferula in laying hens - Özkök, Arda Onur; Kılınç, Gözde (Frontiers in Veterinary Science, 2025)
This study aims to examine the effects of Ferula root powder (FRP) on performance, egg quality, egg oxidant/antioxidant levels, some serum hormone/biochemical parameters, and physical properties of the oviduct in laying hens. A total of 72 (8 replicates, 3 hens/subgroup) laying hens (Nick Brown, 30 weeks) were divided into three groups (FRP-0, FRP-1, FRP-2). During the 9-week trial, FRP-0 (control) was fed with a basal diet (16.88% crude protein, 2,725 kcal/kg metabolizable energy). FRP-1 and FRP-2 groups, however, were fed a diet supplemented with 1 g/kg and 2 g/kg FRP, respectively. The results showed that laying performance, serum hormone (estradiol, progesterone) levels, and some internal organ weights were not affected by FRP supplementation. In comparison to the control group, higher yolk height and yolk index were found in the FRP-added groups. The albumen pH was found to have decreased in FRP-2 group. DPPH radical scavenging activity increased in egg yolk. TBARs value decreased in FRP-1 and FRP-2 groups. Serum triglyceride and cholesterol levels decreased in group FRP-2. Moreover, a higher uterus length was found in the FRP-supplemented group. Given the results achieved, it was determined that FRP does not have a significant estrogenic effect. However, FRP can be utilized to prevent lipid oxidation and for its hypocholesterolemic effect.